An unusual presentation of necrotizing pneumonia caused by foreign body retention in a 20-month-old child: A case report and literature review - Wang, Yuqi; Zhou, Yunlian; Pan, Feng; Wang, Yingshuo (Frontiers in Pediatrics, 2023)
Necrotizing pneumonia(NP) is a rare but serious complication that occurs after foreign body retention. We report a case of severe NP in an infant caused by foreign body retention in the airway with no choking history. Timely tracheoscopy and antibiotic treatment alleviated the infant’s fever and cough. NP can lead to long-term lung function impairment, as seen in this infant who developed bronchiectasis. To reduce the risk of NP resulting from foreign body aspiration, timely diagnosis and treatment are crucial. For patients with airway obstruction and asymmetrical opacity of both lungs, timely diagnostic bronchoscopic evaluation is essential.